The poor and land: A situational analysis of access to land by poor land users in Ghana - Kwapong, T.F.O.A. (Journal of Rural and Community Development 4(1): 51 - 66, 2009)
This write-up looks at the situation of poor land users in Ghana. Specifically literature on poor land users were analyzed to find out how issues affect them and the gaps in literature. There is an identifiable gap in the literature concerning innovation in, for example, chieftaincy institutions and the impact of such innovation on the poor’s access to land which could make it difficult to implement such policies as ‘land banks’, cooperative ownership schemes, and ‘land trusts’. The absence of empirical studies that shed light on the quantitative relationship between incomes and access to land by the poor indicates that policies are likely to be based on guess work and luck. To bridge the gaps in existing literature there is the need to organize thinking along disciplinary lines and identify critical cross-cutting and inter-disciplinary themes supportive of effective policy-making.
Keywords: Land; poor; gender; policy